Bi‐exponential 23Na T2* component analysis in the human brain. (26th February 2018) - Riemer, Frank; Solanky, Bhavana S.; Wheeler‐Kingshott, Claudia A.M.; Golay, Xavier
Abstract : The purpose of this study was to measure the sodium transverse relaxation time T 2 * in the healthy human brain. Five healthy subjects were scanned with 18 echo times (TEs) as short as 0.17 ms. T 2 * values were fitted on a voxel‐by‐voxel basis using a bi‐exponential model. Data were also analysed using a continuous distribution fit with a region of interest‐based inverse Laplace transform. Average T 2 * values were 3.4 ± 0.2 ms and 23.5 ± 1.8 ms in white matter (WM) for the short and long components, respectively, and 3.9 ± 0.5 ms and 26.3 ± 2.6 ms in grey matter (GM) for the short and long components, respectively, using the bi‐exponential model. Continuous distribution fits yielded results of 3.1 ± 0.3 ms and 18.8 ± 3.2 ms in WM for the short and long components, respectively, and 2.9 ± 0.4 ms and 17.2 ± 2 ms in GM for the short and long components, respectively. 23 Na T 2 * values of the brain for the short and long components for various anatomical locations using ultra‐short TEs are presented for the first time. Abstract : Healthy subjects were scanned using 23 Na ultra‐short echo time (UTE) magnetic resonance imaging (MRI) with 18 TEs between 0.17 and 67 ms. T 2 * values were fitted on a voxel‐by‐voxel basis using a bi‐exponential model and using a continuous distribution fit with a region of interest‐based inverse Laplace transform. Detailed 23 Na T 2 * values of the brain for the short and long components for various anatomical locations using UTEs are presented for the first time.